Hubungan Perawatan Payudara Pada Ibu Postpartum Dengan Kelancaran Pengeluaran ASI Di Desa Galak Kecamatan Slahung Kabupaten Ponorogo - Catur Wulandari (Jurnal Delima Harapan, 2018)
Breast care is an act of breast care performed, either by post partum mothers orassisted by others who performed starting on the first day or two after giving birth. Thesmoothness of breast milk and breast beauty after breastfeeding is also dependent care.The purpose of this study was to determine the relationship between breast care in postpartum mothers with a smooth expenditure of milk in Galak Village Slahung DistrictPonorogo Regency.The method used in this study is the description of the correlation, the population inthis study were all postpartum mothers on the third day to six weeks in February-March 2017as many as 31 postpartum mothers. Sampling was done by total sampling technique withsample 31 post partum mother on day 3-6 weeks. Data analysis using Chi-Square analysis.The results of the study most of the respondents (51.6%) have breast care during thepuerperal period is less good. Post partum mother in Galak Village, Slahung Sub-district,Ponorogo Regency mostly (51,6%) have smooth expenditure of breastfeeding. There is arelationship between breast care in post partum mother with the smooth expenditure of milkin Galak Village, Slahung Sub-district, Ponorogo Regency. with p = 0.007.